Екологічні детермінанти вологості стійкого в’янення рослин у дерново-літогенних ґрунтів на лесоподібних суглинках - Жуков, Олександр Васильович; Zhukov, Olexandr; Лядська, І. В.; Lyadsky, I.; Маслікова, Катерина Павлівна; Maslikova, Kateryna (Дніпровський державний аграрно-економічний університет, 2017)
Визначено показники вологості стійкого в’янення рослин дерново-літогенних ґрунтів на лесоподібних суглинках розрахунковим методом та методом вегетаційних мініатюр. Встановлено подібність між двома методами. З’ясовано, що в дерноволітогенних ґрунтах на лесоподібних суглинках вологість стійкого в’янення рослин варіює від 5,33 до 13,19 %. Для дослідженого типу техноземів характерно більш низький показник вологості в’янення рослин у верхніх шарах ґрунту та різке його підвищення в нижніх, що свідчить про більш високу ущільненість шару на глибині 30−40 см і нижче. Доведено, що найбільший вплив на вологість стійкого в’янення рослин має засоленість ґрунту. Регресійний аналіз підтвердив, що обидва методи досліджень дають подібні результати, а отже, побудовані педотрансферні функції дозволяють знизити втрати праці під час визначення даної гідрологічної константи і одержати показник, який має очевидну екологічну значимість. Raising of problem. The steppe zone of Ukraine is characterized by the high concentration of enterprises of ferrous and colored metallurgy. At getting of ores of thousand hectares of the most valuable earth lost during openwork. Problem of proceeding in the ground cover broken because of industrial activity, very sharply stands in the districts of mining. For renewal and return of the broken earth in the agricultural use conduct recultivation that envisages creation in place of exhaust quarries of the artificial ground cover. The special value is acquired by a task to monitoring of water-physical properties of soil as to custom of proceeding in the ecological functions of the ground cover a process control in the process of recultivation. For plants all ground not moisture is accessible, but only and her part, that is contained in soil by forces, less than, than suction force of root hairsprings. A lower limit of availability is humidity of the proof fading of plants. This size is exceptionally important by description and sign of dynamics of proceeding in the broken earth. Loess loams are considered most agronomical a valuable maternal breed. They are characterized by friendly to many agricultural cultures physical properties: by the high coefficient of structuralness, relatively by the optimal closeness of drafting, interparticle, permeability to water. An important problem is development of the methodical going near establishment of ecologically reasonable indexes of humidity of the proof fading of soils that is formed in the process of agricultural recultivation and Loess loams. The aim of our research is to define the indexes of humidity of fading of plants of Sod-lithogenic soils on Loess loams a calculation method and method of vegetation miniatures and to estimate reasons of divergences of these approaches.Materials and research methods. Works are conducted on an experimental area from recultivation of earth, that is on research permanent establishment of theDnepropetrovsk state agrarian-economic university. The standards of soil took away on the layers of 0−10, 10−20, 90−100 cm from the stopped up cut in Sod-lithogenic soil on Loess loams in triple repeated. Taking away of tests is conducted in June-July, 2014. On the basis of size of maximal hygroscopic humidity expected humidity of fading of plants, accepting the translated coefficient 1,34 ‒ after instruction of hydro meteorological service. Except the calculation of humidity of fading of plants on maximal hygroscopic humidity, applied the method of direct determination of index by growing of plantlets in drying glasses and leading to of them to complete fading.Research results. The analysis of the obtained data testifies that the estimations of humidity of fading of plants of soil on the Loess loams got a calculation method vary from 6,54±0,31(a layer is a 0-10 cm) to 12,66±0,19 layer a 90‒100 cm). Between the estimations of humidity of fading of plants a calculation method and method of miniatures is statistically reliable cross-correlation connection(r = 0,98, p = 0,00). Difference between estimations by two methods always positive, that testifies that for the investigational type of tehnozem a calculation method gives understating of estimation, than ecologically correct method of miniatures. One of explanations of such difference Salinization of the ground layer can come forwardDiscussion. The water mode is a key factor that determines the productivity of agroecosystems in the conditions of Steppe of Ukraine. The range of accessible moisture in soil depends on the least moisture-capacity and humidity of fading of plants and determined as a difference between these hydrological constants. Humidity of fading of plants in a most degree depends on grain-size distribution of soil: easy soils are characterized by the less value of it to the index, and more heavy ‒ higher. For this reason the worked out method of determination of humidity of fading of plants for agrozems is based on the count of maximal hygroscopicity by means of universal to the coefficient 1,34 (or 1,5). More ecologically reasonable approach of determination of humidity of fading of plants is a method of miniatures. He is based on direct supervisions on the state plants at the terms of change of humidity of standard of soil. It should be noted that except grain-size distribution on the value of humidity of fading of plants the concentration of salts influences in the ground solution. Results got in the real article also specify on the large informative value of data for mineralization of the ground solution. A new result is establishment of informative role of depth of soil as Predictor of the real value of humidity of the proof fading plants.Conclusion. The got results testify that a calculation method and method of miniatures give the strongly correlating estimations of humidity of the proof fading of plants sufficiently. Index of fading humidity, that is got the method of miniatures is ecologically reasonable, so as directly represents the physiology state of plants depending on content of moisture in soil.
Ecological determinants of humidity of persistent plant wilting in soddy-lithogenic soils on forest loam
Keywords: вологість стійкого в’янення рослин; moisture resistant wilting plants; техноземи; tehnozems; лесоподібні суглинки; lesopodibni loam; рекультивація; reclamation